Regulatory network analyses highlight transcription factor cooperation in haematopoiesis and leukaemogenesis - Harman, JR (2023)
The regulation of gene expression is a complex process that confers cell identity and drives cell differentiation. Transcription factors (TFs) are an important modulator of gene expression and are critical to understanding the regulatory code characterising cell behaviour. However, TFs function in cooperation with one another, acting as a complex combinatorial code to enact gene regulation. Gene regulatory network (GRN) models are used to describe the regulation of genes and to account for this combinatorial code. When the regulatory code underpinning normal cell behaviour goes awry this can lead to abnormal GRNs and the development of disease. This poses two questions: how does TF cooperation drive cellular processes, and how are normal GRNs deregulated in disease?